2007
DOI: 10.1097/psy.0b013e31806bf393
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress After Major Burn Injury

Abstract: Objective-To track the prevalence and stability of clinically significant psychological distress and to identify potentially modifiable inhospital symptoms predictive of long-term distress (physical, psychological, and social impairment).Method-We obtained data from the Burn Model Systems project, a prospective, multisite, cohort study of major burn injury survivors. The Brief Symptom Inventory (BSI) was used to assess symptoms in-hospital (n = 1232) and at 6 (n = 790), 12 (n = 645), and 24 (n = 433) months po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
55
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 118 publications
(58 citation statements)
references
References 60 publications
2
55
0
1
Order By: Relevance
“…This rapid response is brought about by sudden increases in sympathetic nervous system activity and endogenous stress hormone levels [14,50]. It has been reported that the secretions of plasma cortisol, adrenocorticotropic hormone, and aldosterone are significantly increased immediately after severe burns, and the extent of this is associated with intensity of stress [14,40].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This rapid response is brought about by sudden increases in sympathetic nervous system activity and endogenous stress hormone levels [14,50]. It has been reported that the secretions of plasma cortisol, adrenocorticotropic hormone, and aldosterone are significantly increased immediately after severe burns, and the extent of this is associated with intensity of stress [14,40].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the levels of blood glucose, insulin, and cortisol in burn patients are enhanced. In patients with large areas of burn, particularly thirddegree burns, lasting hyperglycemia and hypermetabolism promote secretion from Islets of Langerhans to accelerate glycogenolysis, which elevate blood glucose [14,25,40,51]. Increased levels of cortisols are further associated with enhanced hepatic gluconeogenesis and a reduced insulinmediated glucose uptake into skeletal muscle and adipose tissue [20,44].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations